High-resolution X-ray spectroscopy of the stellar wind in Vela X-1 during a flare - Lomaeva, M.; Grinberg, V.; Guainazzi, M.; Hell, N.; Bianchi, S.; Bissinger, Matthias; Fürst, F.; Kretschmar, P.; Martínez-Chicharro, M.; Martínez-Núñez, S.; Torrejón, J. M. (Astronomy & Astrophysics, 2020)
Context. We present a 130 ks observation of the prototypical wind-accreting, high-mass X-ray binary Vela X-1 collected with XMM-Newton at orbital phases between 0.12 and 0.28. A strong flare took place during the observation that allows us to investigate the reaction of the clumpy stellar wind to the increased X-ray irradiation. Aims. To examine the wind's reaction to the flare, we performed both time-averaged and time-resolved analyses of the RGS spectrum and examined potential spectral changes. Methods. We focused on the high-resolution XMM-Newton RGS spectra and divided the observation into pre-flare, flare, and post-flare phases. We modeled the time-averaged and time-resolved spectra with phenomenological components and with the self-consistent photoionization models calculated via CLOUDY and XSTAR in the pre-flare phase, where strong emission lines due to resonant transitions of highly ionized ions are seen. Results. In the spectra, we find emission lines corresponding to K-shell transitions in highly charged ions of oxygen, neon, magnesium, and silicon as well as radiative recombination continua (RRC) of oxygen. Additionally, we observe potential absorption lines of magnesium at a lower ionization stage and features identified as iron L lines. The CLOUDY and XSTAR photoionization models provide contradictory results, either pointing towards uncertainties in theory or possibly a more complex multi-phase plasma, or both. Conclusions. We are able to demonstrate the existence of a plethora of variable narrow features, including the firm detection of oxygen lines and RRC that RGS enables to observe in this source for the first time. We show that Vela X-1 is an ideal source for future high-resolution missions, such as XRISM and Athena.
CRIS-Team Scopus Importer:2020-10-16
Keywords: Stars: massive; Stars: winds; outflows; X-rays: binaries